2014
DOI: 10.1186/2050-6511-15-3
|View full text |Cite
|
Sign up to set email alerts
|

Rosacea-like facial rash related to metformin administration in a young woman

Abstract: BackgroundSince the skin represents a common site of adverse drug reactions, few data are reported at this time regarding the development of skin rash during the treatment with antidiabetic drugs.Case presentationWe report a 29-year old woman that developed a facial skin rash during the treatment with metformin. Clinical and laboratory findings excluded the presence of systemic diseases, but several diagnosis and many drugs were administered without clinical improvement. The self-dismission of metformin induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
4
6
0
1
Order By: Relevance
“…In agreement with our previous paper [24][25][26], using the Naranjo score, we documented a probable association between adefovir and clinical symptoms.…”
Section: Key Pointssupporting
confidence: 93%
“…In agreement with our previous paper [24][25][26], using the Naranjo score, we documented a probable association between adefovir and clinical symptoms.…”
Section: Key Pointssupporting
confidence: 93%
“…Previously, several authors reported that many factors (e.g. drugs, allergy, bit of animals, parasites) are able to induce skin manifestations [10][11][12][13][14]. In our cases, clinical history suggested that probably Panitumumab could play a role in these skin manifestations.…”
Section: Discussionsupporting
confidence: 51%
“…It is commonly associated with gastrointestinal adverse effects, yet dermatologic reactions to metformin are uncommon and the literature detailing these events and their management is sparse [ 2 ]. Case reports of possible reactions to metformin include erythema multiforme, lichen planus, rosacea, and pseudoporphyria [ 3 – 6 ].…”
Section: Introductionmentioning
confidence: 99%